2008
DOI: 10.1097/mbc.0b013e328300c814
|View full text |Cite
|
Sign up to set email alerts
|

Consensus opinion for the selection and use of therapeutic products for the treatment of haemophilia in Spain

Abstract: The period between isolation of HIV in the early 1980s and the development of effective viral inactivation procedures able to eradicate the virus from the blood supply was long and unfortunately many recipients of blood-derived products became infected; this translated into a devastating impact on their quality of life, quality of care as well as on their life expectancy. Some years later, hepatitis C virus infection was identified as another known blood-borne disease complicating the treatment of haemophilia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…However, until these studies are concluded, we think that it is unjustified to modify the current evidence-based guidelines of most hemophilia organizations which recommend that, where available, rFVIII products are the treatment of choice of hemophilia A patients and that FVIII inhibitors must be tolerized with the same agent used at the time of inhibitor detection [71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…However, until these studies are concluded, we think that it is unjustified to modify the current evidence-based guidelines of most hemophilia organizations which recommend that, where available, rFVIII products are the treatment of choice of hemophilia A patients and that FVIII inhibitors must be tolerized with the same agent used at the time of inhibitor detection [71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…In 1994, the Scientific Committee of the RVEF issued several guidelines to provide physicians treating hemophilia patients throughout the country with clear consensus guidelines for the appropriate choice of factor replacement products. 1 A recent Spanish epidemiological study has estimated that 2518 individuals have hemophilia A and 387 have hemophilia B. 2,3 The estimated prevalence of hemophilia, therefore, would be $1 in 7857 males.…”
Section: Care For Patients With Bleeding Disorders In Spainmentioning
confidence: 99%
“…1,17 The antifibrinolytic drugs tranexamic acid, registered under the name Amchafibrín, and epsilon-aminocaproic acid, registered under the name Caproamín Fides, are both from Rottapharm Madaus, Spain. DDAVP, registered as Minirín for intravenous administration and Octostím as a spray for nasal pulverization (Ferring Laboratories), is the treatment of choice in VWD patients responsive to DDAVP, as determined by a test infusion.…”
Section: Treatment Strategy For Von Willebrand Disease In Spainmentioning
confidence: 99%
“…U pacjentów leczonych czynnikami osoczopochodnymi powinno się stopniowo przechodzić na czynniki rekombinowane [44][45][46]. Zwłaszcza dzieci powinny mieć dostęp do preparatów rekombinowanych.…”
Section: Opinie Ekspertówunclassified